Analisis Hubungan Karakteristik Perusahaan Dengan Kesesuaian Pernyataan Jaminan Pada Laporan Keberlanjutan - Sari Mustika Widyastuti; Esti Tri Endarwati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the relationship between the characteristics of the company and the conformity of the assurance statement in the sustainability report. The accounting information tested in this study is industry sensitivity, profitability, leverage, and company age. This study uses panel data samples (unbalanced) on ASSRAT participating companies on the NCSR website as many as 77 companies for the 2018-2021 period. The analysis technique used is multiple linear regression. The results showed that the variables of industry sensitivity, profitability, leverage, and company age were positively correlated to the statement of assurance of the sustainability report. This explains that the high sensitivity of the industry to the company will encourage the guarantee statement mechanism. The better profitability of the company fosters companies to attract investors to invest. High corporate leverage makes the company motivated to implement a statement of sustainability assurance to restore stakeholder trust. Furthermore, companies that have been operating for a long time will tend to make social disclosures, this recommends the application of a sustainability report assurance statement. The results of this study can theoretically confirm the theory of Stakeholders and Legitimacy which play an essential role in the company's sustainability.